Understanding caregivers’ and community influencers’ perspectives on the barriers to childhood immunisation in Northern Nigerian States with public-private partnerships in routine immunisation programme - Etim, Eno-Obong E.; Odiachi, Angela; Dougherty, Leanne; Alabi, Matthew; Adetunji, Adetayo; Adedimeji, Adebola (BMC public health, 2025)
Background Despite investments by the Nigerian government and international organisations in childhood immunisation to combat child mortality, coverage in many northern states remains below the national average, thereby increasing the risk of vaccine-preventable diseases. This paper examines the barriers to immunisation in six states in northeast and northwest Nigeria, which have the lowest vaccination coverage rates in the country. Method We conducted 24 focus group discussions (FGDs) with mothers/caregivers and community influencers who collaborate with health workers to provide routine immunisation. The socio-ecological framework informed the design of the FGDs. We thematically analysed inductively and deductively coded data on NVivo version 12. Results Barriers to immunisation uptake included: Individual and interpersonal level - limited female mobility, adverse events after immunisation; community level - misconceptions and myths about vaccines, religious beliefs and norms, health provider-patient gender discordance, mistrust of immunisation; system level - poor health worker attitude, ineffective documentation of immunisation appointments, distance to health facilities, inadequate human resource capacity at health facilities, vaccine supply shortages, and lack of incentives. Conclusion This study highlights the intricate barriers to immunisation uptake in northern Nigeria. Key recommendations include engaging male caregivers through tailored social and behavioural change initiatives and capacity building for health workers to improve their counselling skills on vaccine side effects. Findings from the study provide valuable insights for policymakers and programme implementers. Implementing these interventions can tackle ongoing challenges and improve routine immunisation in these states.